Preparation of clindamycin hydrochloride loaded de-esterified low-methoxyl mango peel pectin film used as a topical drug delivery system - Tanpong Chaiwarit (2020)
© 2020 by the authors. In this study, we aimed to develop a low-mexthoxyl pectin (LMP) from mango peel pectin through a de-esterification method for use as a film forming agent. The prepared de-esterified pectin (DP) was compared to commercial LMP (cLMP) which possessed a 29% degree of esterification (DE). Mango peel pectin was extracted from ripe Nam Dokmai mango peel using the microwave-assisted extraction method. Pectin derived from the mango peel was classified as a high mexthoxyl pectin (79% DE) with 75% of galacturonic acid (GalA) content. A de-esterification experiment was designed by central composite design to plot the surface response curve. Our prepared DP was classified as LMP (DE 29.40%) with 69% GalA. In addition, the Fourier-transform infrared spectrophotometer (FTIR) spectra of the DP were similar to cLMP and the pectin backbone was not changed by the de-esterification process. Strikingly, the cLMP and DP films showed non-significant differences between their physical properties (p > 0.05) with respect to the puncture strength (13.72 N/mm2 and 11.13 N/mm2 for the cLMP and DP films, respectively), percent elongation (2.75% and 2.52% for the cLMP and DP films, respectively), and Young's modulus (67.69 N/mm2 and 61.79 N/mm2 for the cLMP and DP films, respectively). The de-esterified pectin containing clindamycin HCl (DPC) and low-methoxyl pectin containing clindamycin HCl (cLMPC) films demonstrated 93.47% and 98.79% of drug loading content. The mechanical properties of the cLMPC and DPC films were improved possibly due to their crystal structures and a plasticizing effect of clindamycin HCl loaded into the films. The DPC film exhibited a drug release profile similar to that of the cLMPC film. Our anti-bacterial test of the films found that the cLMPC film showed 41.11 and 76.30 mm inhibitory clear zones against Staphylococcus aureus and Cutibacterium acnes, respectively. The DPC film showed 40.78 and 74.04 mm clear zones against S. aureus and C. acnes, respectively. The antibacterial activities of the cLMPC and DPC films were not significantly different from a commercial clindamycin solution. The results of this study suggest that mango peel pectin can be de-esterified and utilized as an LMP and the de-esterified pectin has the potential for use as a film forming agent, similar to cLMP. In addition, the remarkable use of de-esterified mango peel pectin to prepare films, as shown by our study, holds a great promise as an alternative material for anti-bacterial purposes.